Clinical features of minor hallucinations in different phenotypes of Parkinson’s disease: A cross-sectional study - Wang, Yaxi; Li, Dongfeng; Chen, Yaning; Zhu, Sha; Jiang, Xu; Jiang, Yinyin; Gu, Ruxin; Shen, Bo; Zhu, Jun; Pan, Yang; Yan, Jun; Zhang, Li (Frontiers in Neurology, 2023)
Background Minor hallucinations (MHs) are the most common psychiatric symptom associated with Parkinson’s disease (PDPsy), but little is known about their characteristics in different motor phenotypes, especially postural instability gait difficulty (PIGD). The aim of this study was to explore the clinical features of MHs in different subtypes of PD. Methods In this cross-sectional study, 213 patients with Parkinson’s disease (PD) were recruited, and the data obtained included comprehensive demographics, motor subtypes, clinical scale scores, and MH contents. Motor subtypes were classified as tremor-dominant (TD), PIGD or indeterminate according to Stebbins’ method. Results A total of 213 PD patients were included: 90 (42.3%) TD patients, 98 (46.0%) PIGD patients and 25 (11.7%) indeterminate. In total, 70 (32.9%) patients experienced MHs. Compared to patients with the TD phenotype, we found that patients with the PIGD phenotype had more severe motor and nonmotor symptoms. They also had a higher incidence of visual illusions (VIs) and a shorter MH latency. Conclusion Our study demonstrated that compared to patients with the TD phenotype, patients with the PIGD phenotype had a higher incidence of MHs, especially VIs, which may lead to a higher incidence of visual hallucinations (VHs). They also had a shorter latency of MHs than patients with the TD phenotype, suggesting an earlier onset of MHs and a worse prognosis.